2022
DOI: 10.1101/2022.01.19.474897
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunotherapy of glioblastoma explants induces interferon-γ responses and spatial immune cell rearrangements in tumor center, but not periphery

Abstract: Recent therapeutic strategies for glioblastoma (GBM) aim at targeting immune tumor microenvironment (iTME) components to induce antitumoral immunity. A patient-tailored, ex vivo drug testing and response analysis platform for GBM would facilitate personalized therapy planning, provide insights into treatment-induced immune mechanisms in the iTME, and enable the discovery of biomarkers of therapy response and resistance. We cultured 47 GBM explants from tumor center and periphery from 7 patients in perfusion … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Recently, we showed that the response to immunotherapy in GBM is indeed region dependent. For this, we cultured GBM explants in perfusion bioreactors and treated with anti-CD47, anti-PD1, or their combination which induced an IFN-γ response only in the tumor center, but not periphery [54]. Adding experimental support to the here described impaired activation signature in the tumor periphery.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, we showed that the response to immunotherapy in GBM is indeed region dependent. For this, we cultured GBM explants in perfusion bioreactors and treated with anti-CD47, anti-PD1, or their combination which induced an IFN-γ response only in the tumor center, but not periphery [54]. Adding experimental support to the here described impaired activation signature in the tumor periphery.…”
Section: Discussionmentioning
confidence: 89%
“…The output clusters corresponded to CNs. To ensure our method was sensitive to rare neighborhoods, we adapted this algorithm by intentionally over-clustering, using k=200 in the K-Means step rather than using a k ranging from 10-20 as used elsewhere (Bhate et al 2021; Phillips, Matusiak, et al 2021; Shekarian et al 2022). Next, to determine which cell types were characteristic of each cluster, we identified, for each cluster, the set of cell-types that were present in more than 80% of the windows allocated to that cluster.…”
Section: Methodsmentioning
confidence: 99%